Identification of CD137-Expressing B Cells in Multiple Sclerosis Which Secrete IL-6 Upon Engagement by CD137 Ligand - Wong, Hiu Yi; Prasad, Ankshita; Gan, Shu Uin; Chua, John Jia En; Schwarz, Herbert (Frontiers in Immunology, 2020)
The potent costimulatory effect of CD137 has been implicated in several murine autoimmune disease models. CD137 costimulates and polarizes antigen-specific T cells towards a potent Th1/Tc1 response, and is essential for the development of experimental autoimmune encephalomyelitis (EAE), a murine model of Multiple Sclerosis (MS). This study aimed to investigate a role of CD137 in MS. Immunohistochemical and immunofluorescence staining of MS brain tissues was used to identify expression of CD137. CD137+ cells were identified in MS brain samples, with active lesions having the highest frequency of CD137+ cells. CD137 expression was found on several leukocyte subsets, including T cells, B cells and endothelial cells. In particular, CD137+ B cells were found in meningeal infiltrates. In vitro experiments showed that CD137 engagement on activated B cells increased early TNF and persistent IL-6 secretion with increased cell proliferation. These CD137+ B cells could interact with CD137L-expressing cells, secrete pro-inflammatory cytokines and accumulate in the meningeal infiltrate. This study demonstrates CD137 expression by activated B cells, enhancement of the inflammatory activity of B cells upon CD137 engagement, and provides evidence for a pathogenic role of CD137+ B cells in MS.